2018
DOI: 10.1007/978-3-319-99740-7_11
|View full text |Cite
|
Sign up to set email alerts
|

Creative Intelligence – Automating Car Design Studio with Generative Adversarial Networks (GAN)

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Radha Krishnan et al [36] proposed a method for creating unique automobile designs from drawings based on a GAN. The authors created a matched data set of approximately 100,000 automobile pictures (with transparent backgrounds) and corresponding drawings to train and test the algorithms.…”
Section: Related Survey On Gan Applicationsmentioning
confidence: 99%
“…Radha Krishnan et al [36] proposed a method for creating unique automobile designs from drawings based on a GAN. The authors created a matched data set of approximately 100,000 automobile pictures (with transparent backgrounds) and corresponding drawings to train and test the algorithms.…”
Section: Related Survey On Gan Applicationsmentioning
confidence: 99%
“…In recent years, some researchers have tried to apply GANs to product designs. For example, Radhakrishnan [23] proposed a GAN-based intelligent vehicle design model, which created new unseen design schemes through the sketches of a car design studio, thereby improving design efficiency. Kularatne [24] proposed a fashion design method combining the expertise of fashion designers and pattern makers by using a GAN on the basis of existing fashion styles to generate new fashion design schemes using existing clothes.…”
Section: Generative Adversarial Networkmentioning
confidence: 99%
“…Figure 10 shows the structure of GAN. We summarized the contribution of GAN to product design as schemes generation [191,192,5], text-to-image synthesis [193], generative transformation [194], collocation generation [195,196,197], sketch acquisition [198,199], colorization [200,201,202], and virtual display [13,203].…”
Section: Product Design Based On Image Datamentioning
confidence: 99%
“…Their results showed that GAN has an excellent ability to learn the color rules of ethnic costumes. Sreedhar et al [5] proposed a car design system based on GAN that supports single-color, dual-color, and multiple-color coloring from a single sketch.…”
Section: Product Design Based On Image Datamentioning
confidence: 99%
See 1 more Smart Citation